The Influence of Job Satisfaction and Work Motivation on Teacher Performance - Sufriyadi (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine the influence of job satisfaction and work motivation on teacher performance. The method used in this study is a quantitative method. The population in this study amounted to 60 respondents (teachers) from three schools from SDIT Fathurrahman, SDIT Tunas Harapan, SDIT Imam Syafi'I in Tembilahan District, Tembilahan Regency, Riau. Data collection in this study was a questionnaire with a Likert scale that has a range of 1-5. The data analysis technique used multiple linear regression analysis. The results of this study first showed that Job Satisfaction has an influence on teacher performance by producing a t count of 0.166 and a t table value of 1.671 (significance level 5%, n = 60). Second, Work Motivation has an influence on Teacher Performance by producing a t count of 0.190. The third job satisfaction and work motivation on teacher performance in SDIT throughout Tembilahan District is 29.1% meaningful or significant. It is known that the R Square value is 0.291. This job satisfaction and work motivation have an influence on teacher performance of 29.1% on the teacher performance variable, while the remaining 70.9% is influenced by other variables not examined in this study.